Determinants of the quality of information disclosed via the Web by small- and medium-sized cooperatives in the Canary Islands - González Aponcio, Zenona (REVESCO. Revista de Estudios Cooperativos, 2020)
The advance experienced by information technologies, and specifically the development of Internet technologies has had its maximum exponent in the progressive deployment of new services and applications for companies, which is leading SMEs to react to the digital transformation of business to adapt to new demands. Within this group of companies are cooperatives that face markets that require more personalized and flexible conceptions of the product or service. In response to these demands, cooperatives have to connect with the environment to capture the needs of customers and partners, and obtain information that helps to meet their needs. For this, it is essential that they are equipped with corporate Web sites that help to generate information and knowledge useful as a support to make decisions and anticipate changes. The objective of this work is to know which are the indicators that explain the quality of the information that small and medium-sized cooperatives in the Canary Islands disclose through the corporate website. To achieve this, it is based on the Delone and McLean model (2002 and 2003) adapted to the websites of 24 cooperatives that are identified using the SABI database and whose data are analyzed by applying the Rasch Model (1980). The results correspond to the total active cooperative Web site and reveal that the quality of information shared by cooperatives through the Web site is based more on information about products and useful information than on information for partners and customers, with some indicatos being conditioned by the province where they are located and the period in which they are created. Therefore, cooperatives should not only value maintaining a corporate website to share complete, up-to-date, relevant and accurate information, but also should communicate and carry out transactions with partners and customers that meet their needs and expectations. The conclusions obtained show that, in general, selected small and medium cooperatives use static and structured Web sites without having evolved towards business portals, and that they miss out on the information they can collect from the site to predict and interpret behaviors of partners and clients, as well as to offer products and services tailored to their preferences.
Keywords: Cooperatives; Internet technologies; Web site; Information; Quality indicators.